REE, Ba, Sr and Rb in the Yamato Meteorites, with Special Reference to Yamato-691(a), -692(b) and -693(c) - Masuda, Akimasa; Tanaka, Tsuyoshi (1978)
P(論文) Following the previous analyses (MASUDA et al., 1977) of Yamato-7301 (j), -7305 (k) and -7304 (m) meteorites for REE, Ba, Sr and Rb, other three meteorites Yamato-691 (a), -692 (b) and -693 (c) were studied here for the same elements, employing the stable isotope dilution. [These three meteorites are enstatite chondrite, Ca-poor hypersthene achondrite and Type III carbonaceous chondrites (NAGATA, 1975).] departmental bulletin paper